Autopoiesis in organization theory and practice - Magalhães, Rodrigo, 1950-; Sanchez, Ron (Emerald, 2009)
"Autopoiesis in Organization Theory and Practice" considers the potential of autopoiesis theory to provide a new unifying framework for the study of organizations as systems and of organizational phenomena as emergent phenomena. The papers in this volume integrate open systems theory with the pioneering work of Maturana and Varela (1980, 1992) on autopoiesis in biological systems. Viewing organizations as living systems opens a powerful new perspective for describing, explaining, and even predicting organizational phenomena across the full spectrum of organizations and environments, from stable to highly dynamic. This collection of papers brings into focus both the great potential and the important challenges facing organizational thinkers in building new organization theory and deriving new principles for management practice based on autopoiesis theory. Topics include the fundamental features of autopoiesis theory, the key conceptual issues surrounding the use of autopoiesis concepts in representing and analyzing organizations as living systems, and the practical applications of autopoiesis theory in designing organizations and managing organizational processes.
Keywords: Organizational sociology.; Autopoiesis.; elektronické knihy; electronic books